The Effect of Promotion Mix on PT. Bank Rakyat Indonesia (Persero) Customer Decisions - Yusuf Rombe (Jurnal Manajemen Bisnis, 2021)
Objectively this study addresses the research formulations, including Does the promotion mix consisting of advertising, personal selling, sales promotion, and public relations have a positive and significant effect on customer decisions at PT. Bank Rakyat Indonesia (Persero), Jakarta branch? From several promotional mix variables, which variable has the most dominant influence on customer decisions to save at PT. Bank Rakyat Indonesia (Persero), Jakarta branch. The data collection method uses a questionnaire, which is distributed to 100 respondents who are customers. Measurement of data using a questionnaire. Based on the research results, the conclusions of this study are advertising, personal selling, and sales promotion have a positive and partially significant effect on customer decisions. In contrast, public relations has no significant impact, and the sales promotion variable is the dominant variable.